NILAI-NILAI PENDIDIKAN MULTIKULTURAL DALAM ALQURAN (Studi Analisis Tafsir Al-Maraghi) - Rahmayani Siregar, Syamsu Nahar, Edi Saputra (At-Tazakki: Jurnal Kajian Ilmu Pendidikan Islam dan Humaniora, 2018)
Abstract: The aims of this research are to analyze in depth about the values of multicultural educationthrough the interpretation of al-Maraghi Qur’an. 1. How is the interpretation of the multicultural versesaccording to Mustafa al-Maraghi ?, 2. What are the values of multicultural education in the Qur’anaccording to Mustafa al-Maraghi’s perspective in the interpretation of al-Maraghi ?, 3. What is the relevancesof multicultural education values contained in the Qur’an with the conditions of modern societytoday? This study uses a qualitative approach to the type of research that is library (Library Research).The data collection was carried out by reviewing the document, namely the interpretation of al-Maraghi.The interpretation of this interpretation uses theMaudhu’I interpretation method. Data analysis techniquesinclude content analysis (Content Anlysis) and critical analysis. The results of this research showedthat: the values of multicultural education include 1) Value of Tolerance, 2) Value of Democracy / Freedom,3) Value of Equality / Equality, 4) Value of Justice. The four values are seen from the aspect of theQur’an found in Q.S. al-Hujurat: 13, Q.S. al-Baqarah verses 213 and 256, Q.S. Nisa verses 1 and 58, andQ.S. al-kafirun: 1-6. According to the researchers’ analysis of the interpretation of al-Maraghi, one of thetriggers of chaos that occurs in social interaction is the attitude of mocking others, so tolerance and mutualhelp are needed in order to be able to live in harmony and humanity.Penelitian ini bertujuan untuk menganalisis secara mendalam tentang nilai-nilai pendidikan multikulturalmelalui tafsir Alquran al-Maraghi. 1. Bagaimana penafsiran ayat-ayat Multikultural menurut Mustahafa al-Maraghi?, 2. Apa sajakah nilai-nilai pendidikan multikultural dalam Alquran menurut perspektif Musthafa al-Maraghi dalam tafsir al-Maraghi?, 3. Apa relevansi nilai-ilai pendidikan multikultural yang terdapat dalamAlquran dengan kondisi masyarakat modern saat ini?. Penelitian ini menggunakan pendekatan kualitatifdengan jenis penelitian yang bersifat kepustakaan (Library Research). Pengumpulan data dilakukan dengantelaah dokumen yaitu tafsir al-Maraghi. Penafsiran pada tafsir ini menggunakan metode tafsirTahlili. Teknikanalisis data meliputi analisis isi (Content Anlysis) dan analisis kritis. Hasil penelitian menunjukkan bahwa:nilai-nilai pendidikan multikultural tersebut antara lain;1) Nilai Toleransi, 2) Nilai Demokrasi/Kebebasan, 3)Nilai Persamaan/Kesetaraan, 4) Nilai Keadilan. Adapun keempat nilai tersebut dilihat dari aspek Alquranterdapat pada Q.S. al-Hujurat:13, Q.S. al-Baqarah ayat 213 dan 256, Q.S. an-Nisa ayat 1 dan 58, dan Q.S.al-kafirun: 1-6. Menurut analisis peneliti terhadap tafsir al-Maraghi, salah satu pemicu kekisruhan yangterjadi dalam interaksi sosial adalah sikap mengolok-olok terhadap orang lain, maka sangat dibutuhkansikap toleransi dan saling tolong menolong secara adil agar mampu hidup dengan rukun dan humanis.Kata Kunci: Pendidikan, Multikultural dan Tafsir al-Maraghi